Overview of Polypharmacy and Drug Interactions in Chronic Kidney Disease Patients at Siloam Hospitals Lippo Village - Pramitaningastuti, Anastasia (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Patients diagnosed with CKD in Indonesia have increased from 2% in 2013 to 3.8% in 2018. Polypharmacy is commonly found in CKD patients, especially in CKD patients with comorbidities. CKD with comorbidities will make the treatment more complex and expensive. This study was conducted to assess the relationship between polypharmacy and drug interactions in CKD patients. Data analysis was carried out descriptively on CKD patients at